IMPACT OF COVID-19 ON ZOOM VIDEO COMMUNICATIONS INC. STOCK PRICE (NOVEMBER 2020 - APRIL 2021) - Julianti Putri, Ika; Lamria Siregar, Suzanna (Dinasti Publisher, 2022)
Coronavirus Disease 2019 (Covid-19) first appeared in the city of Wuhan-China at the end of 2019, then slowly spread throughout the world. This study aims to analyze the stock price movement of Zoom Video Communications Inc (Zm) during the Covid-19 pandemic and the Effect of Covid-19 on the stock price of Zoom Video Communications Inc (Zm).The analytical method used in this research is descriptive quantitative. The analytical tool used in this study is multiple linear regression analysis and hypothesis testing in this study using the t test and F test through the SPSS Version 22 for Windows program.The results show that stock price movements when new cases, total cases, new deaths and total deaths are confirmed, providing information that stock prices tend to rise during Covid-19 cases. New Cases, Total Cases, New Deaths and Total Covid-19 Deaths simultaneously have a significant effect on Stock Prices. Partially New Cases, New Deaths and Total Covid-19 Deaths have a significant effect on Zoom's stock price while the total Covid-19 cases have no significant effect on Zoom's stock prices.